The Effectiveness of Virtual Reality Interventions for Improvement of Neurocognitive Performance After Traumatic Brain Injury: A Systematic Review. Issue 2 (March 2019) - Manivannan, Susruta; Al-Amri, Mohammad; Postans, Mark; Westacott, Laura Jayne; Gray, William; Zaben, Malik
Abstract : Objective: To evaluate current evidence for the effectiveness of virtual reality (VR) interventions in improving neurocognitive performance in individuals who have sustained a traumatic brain injury (TBI). Methods: A systematic literature search across multiple databases (PubMed, EMBASE, Web of Science) for articles of relevance. Studies were evaluated according to study design, patient cohort, VR intervention, neurocognitive parameters assessed, and outcome. VR interventions were evaluated qualitatively with respect to methodology and extent of immersion and quantitatively with respect to intervention duration. Outcomes: Our search yielded 324 articles, of which only 13 studies including 132 patients with TBI met inclusion criteria. A wide range of VR interventions and cognitive outcome measures is reported. Cognitive measures included learning and memory, attention, executive function, community skills, problem solving, route learning, and attitudes about driving. Several studies ( n = 10) reported statistically significant improvements in outcome, and 2 studies demonstrated successful translation to real-life performance. Conclusions: VR interventions hold significant potential for improving neurocognitive performance in patients with TBI. While there is some evidence for translation of gains to activities of daily living, further studies are required to confirm the validity of cognitive measures and reliable translation to real-life performance.